The Da'i's Strategy in Choosing the Right Words for Dakwah - Dinda Aulia; Mira Shaila Ardana; Putri Rahmasari B. Harahap; Fitriani Ritonga; Nasrillah (KOLABORASI: Journal of Multidisciplinary, 2025)
Da’wah is synonymous with the activity of inviting and seducing people, so in carrying out da'wah activities or inviting someone to a path that is approved by Allah, a preacher should choose the right words according to the situation and conditions of his mad’u. The importance of choosing the right words in pearching, such as words that are kind, gentle, and not offensive will help the preaching process to run well and avoid misunderstandings, confusion, offending feelings and so on so that the message conveyed does not reach the mad'u. The research method used in writing this article is library research by collecting several reading results obtained through literature, books, notes or reports of previous research results. The research carried out includes quantitative causality research.